FAKTOR-FAKTOR YANG MEMENGARUHI NILAI PERUSAHAAN SEKTOR MANUFAKTUR - DEWI KURNIA INDRASTUTI (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
Firm value is important for the company because it has an impact on the interest of investors to invest in the company. The company hopes to increase the value of the company in order to prosper shareholders. This study aims to obtain empirical evidence on determinant factors that affect the value of manufacturing sector companies listed on the Indonesia Stock Exchange from 2016 – 2019. Determinant factors used as independent variables are liquidity, leverage, profitability, independent commissioners, audit committees and company’s age. With sample selection techniques using purposive sampling method, 70 companies were obtained as research samples with 280 data. The analysis was conducted with multiple linear regressions; with the results of the research are liquidity, profitability and independent commissioners affecting the firm value, while the leverage, audit committee and age of the company had no effect on the firm value.